Clonal Reproduction of Populus ciliata - Use of most Suitable Parts - Chaukiyal, S. P.; Arya, S. R.; Singh, Ombir (Indian Forester, 1986)
Cuttings were taken from lower, middle and upper 1/3rd parts of the plants and from branches also, to see the height-diameter growth; branches produced by every plant; percentage of plants not attacked by shoot borers; straightness and surviVal. Cuttings from lower and middle one third portions of straight main stem were found best and are recomended for preparing cuttings to raise clones in the nurseries.